Analysis of the Difference in Operational Costs to Production Costs in the Free Nutritious Food (MBG) Program at PT Cibatu Perkasa Abadi - Khairunnisa, Nabila; Gumelar, Taofik Muhammad (Edumedia Solution, 2026)
This report presents the results of internship activities conducted by the author at PT Cibatu Perkasa Abadi with the title Analysis of the Difference in Operational Costs to Cost of Production in the Free Nutritious Food (MBG) Program at PT Cibatu Perkasa Abadi. Observations during the internship activity showed that the management of operational costs in the MBG Cibatu, Ciaul, and Cibadak kitchens still faced differences between the Cost Budget Plan (RAB) and the actual cost. The difference in costs is caused by fluctuations in the price of raw materials, changes in the number of beneficiaries, and different transportation costs at each kitchen location. This condition has a direct impact on changes in the Cost of Production (HPP) of the food produced. During the internship program, the author was directly involved in recording daily operational costs, preparing RAB, calculating HPP, and analyzing the cost difference between budget and realization. This experience provides a real understanding of the importance of cost control, thorough financial recording, and regular budget evaluation to maintain cost efficiency. It is recommended that companies regularly update their budgets, strengthen supervision of cost recording, and improve coordination between operational and financial departments to minimize cost differences and maintain the stability of the MBG Program's HPP.